Design and Simulation Elements of Analytical Microsystem-on-Chip With the Structures "Silicon-on-Insulator" - Dovgiy, V.V.; Kohut, I.T.; Golota, V.I. (Physics and Chemistry of Solid State, 2016)
In this paper the results of architecture development, layout designof analytical microsystem-on-chip with the structures "silicon-on-insulator" (SOI) and its elements schemotechnical computer simulation for determine their electrical and time characteristics are presented.